Generative AI in Teaching and Learning: Benefits and Challenges - Silwal, Umesh; Kafle, Rudra; Dhungana, Ramesh (Journal of Nepal Physical Society, 2025)
Recent advancements in Artificial Intelligence (AI), particularly Generative AI (GenAI), have brought both transformative opportunities and significant challenges to the future of teaching and learning practices. This article provides an overview of popular GenAI tools and explores strategies for integrating them into classroom instructions, their ethical considerations, and challenges. This work includes narratives of implementation demonstrating how specific GenAI tools were utilized by the authors, including the use of ChatGPT for drafting an assignment, NotebookLM for curating content, developing formative assessments, and providing study materials for students, and the application of AI-integrated assessment tools like Gradescope to streamline grading in large classes. In addition, we present a summary of guidelines for educators and institutions to ensure the responsible and effective use of GenAI in educational settings. While GenAI offers powerful possibilities for enhancing teaching and learning, the human element remains irreplaceable. The role of the teacher must shift from being the sage on the stage to the guide on the side, providing authentic, AI-enhanced learning experiences. To succeed in this evolving educational landscape and prepare for the future workforce, students require intrinsic motivation, emotional intelligence, and meaningful human connections, in addition to their technical skills.